2021
DOI: 10.1002/adfm.202008720
|View full text |Cite
|
Sign up to set email alerts
|

Copper Clusters: An Effective Antibacterial for Eradicating Multidrug‐Resistant Bacterial Infection In Vitro and In Vivo

Abstract: Infections caused by multidrug-resistant (MDR) bacteria pose a threat to human health worldwide, making new effective antibacterial agents urgently desired. To date, it is still a great challenge to develop new antibiotics for MDR bacteria with clear antibacterial mechanisms. Herein, a novel alternative antibacterial copper clusters (CuCs) molecule is precisely synthesized utilizing an artificially designed theanine peptide. The prepared CuCs exhibit excellent broad-spectrum antibacterial activity in vitro, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
100
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(102 citation statements)
references
References 73 publications
1
100
0
1
Order By: Relevance
“…The antibacterial activity of the ASE NPs was also observed by a live/dead cell assay using SYTO@9 and PI fluorescent dye. Green/red bacterial cells were considered to be live/ dead cells with intact/damaged membranes, 47 which is a direct reflection of bacterial death. Fluorescence assays were performed by 488 nm laser excitation and 530 nm emission filters for SYTO 9 (live staining).…”
Section: Fluorescence Detection Of the Antibacterial Activitymentioning
confidence: 99%
“…The antibacterial activity of the ASE NPs was also observed by a live/dead cell assay using SYTO@9 and PI fluorescent dye. Green/red bacterial cells were considered to be live/ dead cells with intact/damaged membranes, 47 which is a direct reflection of bacterial death. Fluorescence assays were performed by 488 nm laser excitation and 530 nm emission filters for SYTO 9 (live staining).…”
Section: Fluorescence Detection Of the Antibacterial Activitymentioning
confidence: 99%
“…Cu clusters prepared using an artificially designed theanine peptide exhibited strong in vitro antibacterial effects against MRSA, S. aureus, S. epidermidis , E. coli and P. aeruginosa due to the destruction of the bacterial wall structure and inhibition of the activity of glutathione reductase associated with ROS outburst, which can result in bacterial death. An in vivo study using Cu clusters revealed their beneficial impact on healing skin wound infections and sepsis caused by MRSA in mice, achieving therapeutic effectiveness comparable with that of mupirocin ointment and VAN along with very low cytotoxicity to normal mammalian cells [ 300 ].…”
Section: Applied Nanomaterialsmentioning
confidence: 99%
“…Third, there are number of novel antimicrobial materials that should be investigated for their suitability to be formulated into a suitable form to be used as additives for an AFAMBC. Examples of materials that could be added to the powder of a plain cement are a quorum-sensing inhibitor drug[ 113 ], Ti-doped ZnO[ 114 ], nano-GO nanosheets[ 115 ], selenium nanoparticles[ 116 ], Ag-nanoparticle-reduced GO nanocomposite[ 117 ], chitosan hybrid nanoparticles[ 118 ], a Cu cluster molecule[ 119 ], powder prepared from extract from a Tunisian lichen[ 120 ], Yb-doped ZnO nanoparticles[ 121 ], and an analog of PKZ18 (PKZ18-22), a molecule that has been shown to block growth of antibiotic-resistant S. aureus in biofilm[ 122 ]. Examples of materials that could be added to the liquid of a plain cement are benzothiazole or one of its derivatives[ 123 , 124 ] and a natural antimicrobial agent (such as extract of Salvadora persica , Olea europaea , and Ficus carcia leaves[ 125 ] or biosynthesized ZnO nanoflowers[ 126 ]).…”
Section: Future Prospectsmentioning
confidence: 99%